Interventions to optimise the care continuum for chronic viral hepatitis: a systematic review and meta-analyses. Issue 12 (December 2016) - Zhou, Kali; Fitzpatrick, Thomas; Walsh, Nick; Kim, Ji Young; Chou, Roger; Lackey, Mellanye; Scott, Julia; Lo, Ying-Ru; Tucker, Joseph D
Summary: Background: Advances in therapy for hepatitis B virus (HBV) and hepatitis C virus (HCV) have ushered in a new era in chronic hepatitis treatment. To maximise the effectiveness of these medicines, individuals must be engaged and retained in care. We analysed operational interventions to enhance chronic viral hepatitis testing, linkage to care, treatment uptake, adherence, and viral suppression or cure. Methods: We did a systematic review of operational interventions, and did meta-analyses for sufficiently comparable data. We searched PubMed, Embase, WHO library, International Clinical Trials Registry Platform, PsycINFO, and CINAHL for randomised controlled trials and controlled non-randomised studies that examined operational interventions along the chronic viral hepatitis care continuum, published in English up to Dec 31, 2014. We included non-pharmaceutical intervention studies with primary or secondary outcomes of testing, linkage to care, treatment uptake, treatment adherence, treatment completion, treatment outcome, or viral endpoints. We excluded dissertations and studies of children only. Data were extracted by two independent reviewers, with disagreements resolved by a third reviewer. Studies were assessed for bias. Data from similar interventions were pooled and quality of evidence was assessed using GRADE. This study was registered in PROSPERO (42014015094). Findings: We identified 7583 unduplicated studies, and included 56 studies that reported outcomes along the care continuum (41 for HCV and 18 for HBV). All studies except one were from high-income countries. Lay health worker HBV test promotion interventions increased HBV testing rates (relative risk [RR] 2·68, 95% CI 1·82–3·93). Clinician reminders to prompt HCV testing during clinical visits increased HCV testing rates (3·70, 1·81–7·57). Nurse-led educational interventions improved HCV treatment completion (1·14, 1·05–1·23) and cure (odds ratio [OR] 1·93, 95% CI 1·44–2·59). Coordinated mental health, substance misuse, and hepatitis treatment services increased HCV treatment uptake (OR 3·03, 1·24–7·37), adherence (RR 1·22, 1·05–1·41), and cure (RR 1·21, 1·07–1·38) compared with usual care. Interpretation: Several simple, inexpensive operational interventions can substantially improve engagement and retention along the chronic viral hepatitis care continuum. Further operational research to inform scale-up of hepatitis services is needed in low-income and middle-income countries. Funding: World Health Organization and US Fulbright Program.